Duloxetine ameliorates valproic acid‐induced hyperactivity, anxiety‐like behavior, and social interaction deficits in zebrafish. Issue 1 (3rd October 2021) - Joseph, Thomson Patrick; Zhou, Fang; Sai, Liu Yang; Chen, Hanyu; Lin, Stanley Li; Schachner, Melitta
Abstract: Syndromic autism spectrum disorders (ASDs) are characterized by impaired social communication and repetitive/stereotyped behaviors. Currently available therapeutic agents against ASD have limited efficacy. Thus, searching for novel and effective drugs ameliorating core symptoms, in particular social deficits, is of utmost importance. Duloxetine (DLX), an antidepressant that has been identified as an agonist mimetic for the cell adhesion molecule L1, exhibits beneficial functions in vitro and in vivo. Therefore, in this study, we focused on the rapid and persistent neuroprotective function of DLX following valproic acid (VPA)‐triggered hyperactivity, anxiety‐like behavior and social deficits in zebrafish. Embryonic exposure to VPA reduced survival in a dose‐ and time‐dependent manner, delayed hatching, and also resulted in a significant number of malformed larvae. After initial dose–response experiments in zebrafish larvae, 10 μM VPA exposure between 0.33 and 4.5 days post fertilization (dpf) was identified as an effective concentration that led to an early and persistent ASD‐like phenotype in zebrafish. ASD‐like elevated acetylcholine esterase (AChE) activity and reduced Akt–mTOR signaling was observed in zebrafish whole brain. Acute administration of DLX (4.5–6 dpf) reduced the VPA‐induced ASD‐like phenotype in zebrafish larvae. Additionally, such early‐life acute DLX treatment had long‐term effects in ameliorating social impairments, hyperactivity, and anxiety‐like behaviors through adulthood. This was accompanied by reduced AChE activity and by normalized Akt–mTOR signaling. Overall, DLX treatment showed a long‐term therapeutic effect on autistic‐like behaviors, and alteration of AChE activity and Akt–mTOR signaling were identified as crucial in the VPA‐induced ASD zebrafish model. Lay Summary: Autism spectrum disorder (ASD) is a neurological condition with limited treatment options. Affected individuals experience trouble with speech, interpersonal interaction, and repetitive movements. We used a valproic acid‐induced ASD model in zebrafish and tested if duloxetine could reduce some aspects of ASD. Duloxetine reduced core ASD features, highlighting it as a potential therapeutic agent to ameliorate some features of autism in humans.